Effect of immersion duration of trichoderma harzianum on local chili growth - Dini Puspita Yanty; Siti Hardianti Wahyuni (Talenta Publisher, 2019)
Effect of immersion duration of trichoderma harzianum on local chili growth the aim of this researchis to see the old soaking ability of Trichoderma harzianum mushroom on the growth of local chili.The design used was a Completely Randomized Design (CRD) consisting of 6 treatments and 4replications, namely local chili seeds soaked with a 5-minute T.harzianum suspension, local chiliseeds soaked with a 10-minute T.harzianum suspension, local chili seeds that were soaked marinatedwith T.harzianum suspension for 15 minutes, local chili seeds soaked with T.harzianum suspensionfor 20 minutes, local chili seeds soaked with T.harzianum suspension for 25 minutes, Control (withoutimmersion with trichoderma harzianum suspension. Observed parameters are the percentage of local chiligrowth, plant height and number of leaves The results showed that the application of trichoderma harzianumhad a good effect on the growth of chili plants, soaking for 25 minutes was the best soaking on localchili seeds.